Penggunaan Filler Buton Rock Asphalt dan Limbah Ethylene Vinyl Acetate Pada Aspal Pen. 60/70 Terhadap Stabilitas Campuran Beton Aspal - nanda rizka amalia; Sofyan M. Saleh; Lulusi Lulusi (Journal of The Civil Engineering Student, 2020)
One of the things that damage and weaken the highway flexible pavement is caused by the low strength and low durability of the Asphalt Concrete-Wearing Course (AC-WC) layer prompted by flood water coming from overflown river water or poor drainage system. One of the alternative is to do a modification on the concrete asphalt mixture by substituting the filler using Buton Rock Asphalt (BRA). In addition, the use of Ethylene Vinyl Acetate (EVA) polymer waste as the substitution of bitumen (additive). The purpose of this study was to determine the effect of the usage of EVA waste as an additive to asphalt pen 60/70 and the substitution of BRA as a filler on the characteristics of the AC-WC mixture. This study began by finding the optimum bitumen content (OBC). Then the manufacture of the test specimen was done with a combination of Ethylene Vinyl Acetate (EVA) polymer waste amounted to 3%; 5% and 7% towards the asphalt. The best results of the stability test in the normal water immersion with the BRA substitution had met the specifications of 1000 kg of 1450,78 kg on a percentage of BRA 50%, and the best stability value with the EVA substitution was amounted to 1655,79 kg on the percentage of EVA 3%. On the muddy water immersion, the best stability value with the BRA substitution amounted to 1476,34 kg on a percentage of BRA 50%, and the best stability value with the EVA substitution was amounted to 1695,39 kg on the percentage of EVA 3%.